A review of melting and freezing processes of PCM/nano-PCM and their application in energy storage. (15th November 2020) - Rostami, Sara; Afrand, Masoud; Shahsavar, Amin; Sheikholeslami, M.; Kalbasi, Rasool; Aghakhani, Saeed; Shadloo, Mostafa Safdari; Oztop, Hakan F.
Abstract: Phase change materials (PCMs) are capable of storing energy as latent energy by changing the phase and provide the stored energy when they are returned to their initial phase at a desired time. Due to the varying melting temperature of these materials, their application in air conditions of buildings, as well as the provision of hygienic hot water has received much attention, recently. This paper first provides a detailed illustration of phase change materials and their working principle, different types, and properties. Then a characteristic example of PCMs in solar energy storage and the design of PCMs are reviewed and analyzed. Next, this paper focuses on the heat transfer, melting and freezing processes of PCM/nano-PCMS including different models and experimental research on the natural convection and thermal energy storage. Finally, some challenges and suggestions are presented following the conclusion of this article. It is found that these materials generally improve system efficiency. Without using mechanical equipment, these materials are naturally adapted to the temperature fluctuations of the environment, leading to a reduction in energy consumption and subsequently energy management.